Design of A Web-Based Online Disposition Information System Case Study: Medan City Police - Dewi, Hartika Sari; Zakir, Ahmad; Abdullah, Arif (Electronic Integrated Computer Algorithm Journal, 2025)
In the digital era, efficiency in managing information is crucial, especially within the police force. The Medan City Police require an information system that can support a fast and integrated mail disposition process. This study designed and built a web-based Online Disposition Information System using the Waterfall method. The system design includes a responsive interface and an appropriate database structure. Testing used the Black Box method to ensure the accuracy of input and output. This application was developed with PHP and MySQL. The results show that the system facilitates Medan City Police personnel in receiving, processing, and tracking incoming mail efficiently.